A Socio-economic Analysis on Shrimp Culture (Litopenaeus vannamei) in Godavari Districts of Andhra Pradesh, India - , Chowdula Shireesha, C. Prabakar (Archives of Current Research International, 2024)
Shrimp is a major exportable commodity, with high demand and prices on the international market. Andhra Pradesh is one of India's maritime states, with 974 kilometres of coastline. The state is the leading producer and exporter of farmed shrimp. Although shrimp farming has been practiced for many decades, a number of challenges that need to be addressed in order to improve the overall efficiency of the shrimp industry. In light of this, the present study was carried out to analyse the socio-economic status of shrimp farming in the East and West Godavari Districts of Andhra Pradesh. The data subjected to economic analysis revealed that the profitability of the venture in the study area. The estimates of Cobb-Douglas production function analysis showed that, stocking density, feed, probiotics and feed supplements, labour, and season dummy has significant influence on the shrimp yield. The estimates of resource use efficiency revealed the under-utilization of inputs, highlighting the need for optimising the use of resources to increase profitability. The returns to scale in shrimp culture of 1.04 indicates increasing returns to scale in production.